L’examen collaboratif : étude de cas en contexte universitaire finlandais - Ana-Maria Cozma (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Following a collaborative exam, the undergraduate students of the French department of the University of Turku (Finland) were asked to express their opinions and perceptions of this kind of examination. I first provide a global view of the forms that collaborative exams can take. Then, I present this particular collaborative situation and analyse it based on the students’ feedback in a survey. I pay particular attention to the behaviour adopted by the students during the collaborative exam, as well as to their representation of this innovative means of evaluation. In response to the difficulties experienced by the students, I suggest a series of solutions meant to improve the process of collaborative evaluation.